Strategies to impact swine feed biosecurity - Stewart, Savannah C (Kansas State University, 2020)
Heightened concern surrounding pathogen spread within animal food manufacturing and farm facilities has led to increased interest in monitoring techniques. A series of two experiments were conducted to determine the impact of four different environmental swab types on the detection of Porcine Epidemic Diarrhea Virus (PEDV) on two different surfaces (stainless steel and woven polyethylene totes), and then determine the differences in detection of PEDV in soybean meal (SBM) between environmental swabbing, individual probe sampling, and composite probe sampling. The first experiment demonstrated a dose × surface type × swab type interaction (P<0.0001; SEM=0.96), with Dacron-tip and cotton gauze swabs yielding the most detectable PEDV from the surfaces. The second experiment utilized miniature totes of SBM inoculated with a small amount of PEDV to compare detection rates between environmental sampling, individual probe samples, and composite probe samples. It was determined that 37% of individual probe samples, 33% of environmental swabs, and 100% of composite probe samples found to contain viral RNA, demonstrating the inability for individual samples to dependably detect the presence of viral contamination. Subsequently, the environmental monitoring techniques identified in Experiment 1 were used to monitor and both a multiple-stage swine operation and the feed mill supplying it during an outbreak of PEDV. Data were collected throughout the duration of the outbreak and was used as an informational tool for employees and to monitor efficacy of cleanup efforts. The changes in viral presence as detected by PCR throughout the duration of the outbreak illustrate how differences in biosecurity procedures and employee behavior can impact clean-up efforts, and the ability of environmental monitoring to be used as a tool during a disease outbreak. A study conducted during this specific outbreak evaluated the presence of Enterobacteriaceae when compared to PEDV and rotavirus utilizing environmental sampling, as well as a comparison of two different testing methods for Enterobacteriaceae (a traditional laboratory culture analysis and a “rapid” on-site detection method). This study noted differences in mean reported PEDV Ct values throughout different areas on-farm, with lower values noted in areas with pig contact, non-pig contact, and within the main office area of the farm, while the feed mill had no environmental samples show PEDV presence throughout the duration of the study. There was no evidence of correlation noted (r ≤ 0.20, P > 0.05) between the presence of PEDV or rotavirus and the presence of Enterobacteriaceae, however he “rapid” Enterobacteriaceae test had a significantly strong correlation (r = 0.65, P < 0.0001) with the cultured testing results, indicating that it could be used to monitor levels on-farm as an alternative to laboratory culturing methods. A second study was conducted in Brazil to identify Enterobacteriaceae presence within the feed manufacturing facilities of a multi-farm system experience a viral outbreak. Zone 5 had the lowest growth outside of feed and ingredient samples collected. Similar growth was noted in zones 1,2,3,4, 6 as well as the highest levels of growth in groups 2,3,4, 6 and 7. There was a moderate correlation found between different zoned areas of the feed manufacturing facilities and level of Enterobacteriaceae growth, suggesting that there is potential for the use of Enterobacteriaceae monitoring to help facilities determine areas of concern for facility hygiene or biosecurity practices.
Keywords: biosecurity; feed; swine; enterobacteriaceae; virus; environmental monitoring